Framing Immigration and Integration : Relationships between Press and Parliament in the Netherlands - Vliegenthart, Rens and Roggeband, Conny (International Communication Gazette, 2007)
This article examines how the salience and framing of political issues in the press and in parliament influence each other and how this salience and framing is influenced by key events outside the media and parliamentary realms. The case focused on is the debate on immigration and integration in the Netherlands between 1995 and 2004. The empirical analyses are based on a computer-assisted content analysis of both parliamentary documents and newspaper articles. Results show bidirectional causal relationships between media and parliament. In the case of salience only long-term influence relationships are found, while framing influences follow an interesting pattern: an increase in the use of a frame in one arena leads to an increase in the other arena only if this frame has already been used regularly in the latter arena. External events have more considerable and consistent impact on issue salience and framing in both arenas.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ4MDQ4NTA3MDc2NTgy